PROGRAMMED OBSOLESCENCE: products with time set to die - Barão Junior, Gilberto Augusto; Soares, Nathalia Maria (Revista Interface Tecnológica, 2020)
This article addressed the concepts of programmed obsolescence, a phenomenon that, according to research, arose in the early 20th century, with the use of pre-defining conditions of the useful life of a product, service, or durable things. It was observed that this form of administration was left to us by inheritance from the primary administration, having a direct connection with a theory of scientific management by Henry Ford and with an automobile industry, which at that time, to keep the market warm, began to run out of production products. The types of programmed obsolescence, how it interferes in our lives, theories that establish its presence or not in the present day and the disorders that it created and still brings, mainly to the environment, have been studied. Bibliographic searches were the bases for such understading.